Cross-cultural adaptation, evaluation and validation of the Spouse Response Inventory: a study protocol. Issue 10 (14th October 2014) - Kaiser, Ulrike; Steinmetz, Dorit; Scharnagel, Rüdiger; Jensen, Mark P; Balck, Friedrich; Sabatowski, Rainer
Abstract : Introduction: Since the response of spouses has been proven to be an important reinforcement of pain behaviour and disability it has been addressed in research and therapy. Fordyce suggested pain behaviour and well behaviour be considered in explaining suffering in chronic pain patients. Among existing instruments concerning spouse's responses the aspect of well behaviour has not been examined so far. The SRI (Spouse Response Inventory) tries to consider pain behaviour and well behaviour and appears to be acceptable because of its brevity and close proximity to daily language. The aim of the study is the translation into German, followed by evaluation and validation, of the SRI on a German sample of patients with chronic pain. Methods and analyses: The study is comprehensively designed: initially, the focus will lie on the translation of the instrument following the guidelines for cross-cultural translation and adaptation and evaluation of the German version according to the source study. Subsequently, a validation referring to predictive, incremental and construct validation will be conducted using instruments based on similar or close but different constructs. Evaluation of the resulting SRI-G (SRI-German) will be conducted on a sample of at least 30 patients with chronic pain attending a comprehensive pain centre. For validation at least 120 patients with chronic headache, back pain, cancer related pain and somatoform pain disorder shall be included, for a total of 480 patients. Separate analyses according to specific pain diagnoses will be performed to ensure psychometric property, interpretability and control of diagnosis of specific limitations. Analyses will include comprehensive investigation of psychometric property of the scale by hierarchical regression analyses, correlation analyses, multivariate analysis of variance and exploratory factor analyses (SPSS). Ethics: The study protocol was approved by the Ethics Committee of the University of Dresden (EK 335 122008) based on the Helsinki declaration.